Liposomal irinotecan pre-emptive dose reduction in patients with pancreatic ductal adenocarcinoma: 667 patients’ experience within a population-based study - Tai-Jan Chiu (SAGE Publishing, 2021)
Background: Liposomal irinotecan (nal-IRI) plus 5-fluorouracil and leucovorin (5-FU/LV) is currently the standard second-line treatment for patients with pancreatic ductal adenocarcinoma (PDAC) after previous failed gemcitabine-based therapy. This population-based study aimed to evaluate the efficacy and safety of nal-IRI + 5-FU/LV and the association of pre-emptive nal-IRI dosing with treatment outcomes in patients with PDAC. Methods: We retrospectively enrolled a total of 667 consecutive patients with PDAC who received nal-IRI plus 5-FU/LV treatment between August 2018 and November 2020 at 9 medical centers in Taiwan. Patients were allocated into groups according to pre-emptive nal-IRI dosing (⩾75%, 50–74%, <50%) for comparison of treatment efficacy and safety. Results: The median overall survival (OS) and time to treatment failure (TTF) were 5.9 months [95% confidence interval (CI), 5.3–6.5] and 2.8 months (95% CI, 2.6–3.0), respectively. The median OS was 6.5 months (95% CI, 5.7–6.7), 5.0 months (95% CI, 3.4–6.5), and 4.1 months (95% CI, 2.7–5.6), respectively, among the ⩾75%, 50–74%, and <50% pre-emptive nal-IRI dosing groups, whereas the median TTF of the three groups was 3.0 months (95% CI, 2.6–3.4), 2.6 months (95% CI, 2.3–2.9), and 1.9 months (95% CI, 1.6–2.2), respectively. Pre-emptive nal-IRI dosing <50% was an independent negative prognostic factor for OS and TTF in multivariate analyses. The most common severe adverse events were neutropenia (22.9%), anemia (21.1%), and hypokalemia (15.4%). Patients in the <50% pre-emptive nal-IRI dosing group had a significantly lower incidence of neutropenia and non-neutropenic infection than those in the other groups. Conclusion: Our results support the use of nal-IRI + 5-FU/LV as standard clinical practice for treating patients with PDAC based on this large population-based study. Our findings encourage physicians to provide adequate doses of nal-IRI in order to achieve better outcomes without compromising safety profiles.